What are the factors that define a Kenyan identity? The case of Kenyan Asians - Muraj, Hital (Graduate School of Business (GSB), 2025)
In Kenya, tribalism and ethnicity have wielded considerable influence over social, political, and economic dynamics. A notable milestone in the pursuit of inclusivity occurred on July 21, 2017 (Appendix V), when former President Uhuru Kenyatta officially designated the Kenyan Asian community as the 44th tribe, marking a significant stride toward fostering unity. This step held immense significance as tribal identity serves as the bedrock of Kenyan national identity, and the acknowledgement of Kenyan Asians as a legitimate demographic group represented substantial progress. In light of this development, the present research is dedicated to formulating a praxis model for a social movement aimed at rationalizing the social integration of Kenyan Asians. This endeavour entails a comprehensive exploration of their identities, perspectives, attitudes, concerns, and aspirations, facilitated through the effective utilization of digital platforms, forums, and the Internet. The research engaged a total of 147 participants, with 27 participating in face-to-face interviews and the remaining 120 completing online surveys. This diverse sample encompassed individuals from indigenous Kenyan tribes as well as Kenyan Asians, spanning an age range from 18 to 77 years. Methodologically, the study adopted an ethnographic approach that combined grounded theory and inductive reasoning. Edwards' phenomenological research methodology was additionally employed to gain deeper insights into the everyday experiences of the target population while mitigating preconceived researcher biases. The inclusive innovation praxis model aims to foster a racially inclusive, diverse, and equitable nation. The research's culmination highlighted that Kenyan Asians recognize the country's immense potential for achieving its economic growth objectives. A significant proportion of the Kenyan Asian participants represented second, third, and fourth generations, exhibiting diversity in education, political affiliations, and professions. Notably, the Kenyan Asian community played a pivotal role in Kenya's struggle for independence and identifies as Kenyan by birth with Indian ancestry. However, despite their historical contributions, tensions and a lack of acceptance persist among Kenyan Africans towards the Kenyan Asian community. Many Kenyan Asians perceive the 'Tribe 44' designation as primarily politically motivated and offering limited tangible benefits. On the other hand, Kenyan Africans contend that Kenya struggles with unity across its numerous tribes and sub-tribes, which constitute the national identity. Personal identities vi among Kenyan Africans are closely tied to their tribal affiliations. Furthermore, perceptions of economic exploitation, stemming from the colonial era, persist, with some Kenyan Africans viewing Kenyan Asians as "thieves" and the colonial system as designed to perpetuate African subjugation. Race, religion, food, politics, and marriage also emerge as contentious points, with religion posing the most significant challenge. The study responds to these challenges by developing a praxis model for fostering integration between these two communities. Additionally, it outlines a business model canvas encompassing six dimensions: challenge, inclusivity, innovation, practicability, sustainability, and prototype. The study advocates for equal access to social, political, and economic opportunities, underscoring the importance of dismantling structural biases and prejudices. To achieve inclusivity, the involvement of multiple stakeholders is essential, including the general public, political leaders, media, educators, corporate figures, and individuals of Kenyan Asian descent. The study further recommends the deployment of various online tools, such as websites, Facebook Groups, Twitter, Instagram, WhatsApp/Telegram, SMS, newsletters, video chats, podcasts, and workshops, as part of a comprehensive innovation strategy encompassing understanding, translation, adoption, and internalization.